2019
DOI: 10.1111/nmo.13632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citalopram on esophageal motility in healthy subjects—Implications for reflux episodes, dysphagia, and globus

Abstract: Background Drugs such as citalopram, “targeting” the serotonin pathway, can alter esophageal mechano‐chemical sensitivity and gastrointestinal motility. The aim of this study was to clarify the effect of citalopram on esophageal motility and sphincter function, transient lower esophageal sphincter relaxations (TLESRs), and reflux events. Methods Sixteen healthy volunteers (HV) receiving 20 mg citalopram or placebo intravenously, in a randomized cross‐over fashion, underwent two high‐resolution impedance manome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
9
1
1
Order By: Relevance
“…However, in this study the IGP could not be measured due to disturbing noise at the HRiM measurements in the preprandial period. In the current study, was an adaptation period of 30 min before consumption of the meal, whereas in the study by Manolakis et al, 28 the adaptation period lasted 85 min, leaving us to believe that 30 min is not enough time for the esophagus and proximal stomach to adapt to the HRiM probe leading to noise in the HRiM tracings. Therefore, we cannot assume that the administration of denatonium benzoate has led to a change in IGP profile in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…However, in this study the IGP could not be measured due to disturbing noise at the HRiM measurements in the preprandial period. In the current study, was an adaptation period of 30 min before consumption of the meal, whereas in the study by Manolakis et al, 28 the adaptation period lasted 85 min, leaving us to believe that 30 min is not enough time for the esophagus and proximal stomach to adapt to the HRiM probe leading to noise in the HRiM tracings. Therefore, we cannot assume that the administration of denatonium benzoate has led to a change in IGP profile in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…También se ha asociado con presiones elevadas del esfínter esofágico superior y sensación de globus, por lo que debe usarse con precaución en pacientes con globus asociado. 146 La teofilina, un antagonista de la adenosina que relaja el músculo liso y tiene propiedades analgésicas viscerales, fue evaluada en dos estudios del grupo de Rao. Los autores demostraron que este fármaco aumentó los umbrales de percepción del dolor en pacientes sometidos a distensión esofágica con balón.…”
Section: Otros Fármacosunclassified
“…48 The most recent randomized placebo-controlled cross-over study in 16 healthy volunteers undergoing HRM found citalopram significantly reduced the DCI, increased the upper esophageal resting pressure, increased the integrated relaxation pressure, and reduced TLESRs. 49 Further study is needed to understand the effects on SSRIs on esophageal innervation and motility.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%